Outcomes in persistent hyperplastic primary vitreous. Issue 7 (17th June 2005) - Hunt, A; Rowe, N; Lam, A; Martin, F
Abstract : Aims: To report outcomes in cases of persistent hyperplastic primary vitreous (PHPV) and examine factors predictive of visual acuity in patients selected for surgery. Methods: Retrospective case series of 55 eyes in 50 patients presenting between 1990 and 2001 at the Children's Hospital, Westmead. 33 eyes underwent surgery aimed at visual rehabilitation. Results: In surgical patients, median age at surgery was 77 days, and median age at final follow up was 28 months. Six (18%) achieved a visual acuity at final follow up of 6/60 or better and eight (24%) achieved acuity of less than 6/60 to counting finger vision inclusive. Those undergoing surgery before 77 days were approximately 13 times more likely to obtain a visual acuity of counting fingers or better than those operated later (p = 0.01). Neither posterior segment PHPV nor post-surgical glaucoma was a significant predictor of outcome in this selected group. Conclusion: Early surgery aimed at rehabilitation markedly improves the likelihood of useful visual outcome in selected eyes with PHPV.